Transport capacity of flow in earthline channels - Arifjanov, Aybek; Samiyev, Luqmon; Xoshimov, Sardor; Shaymardanov, Samandar; Tadjiboyev, Suhrob (E3S web of conferences, 2023)
The theory of river flow transport is the major cause of the development of the irrigation sector and largely determines the stability of the irrigation scheme. Crop water requirements vary due to climate and crop growth stages. For this reason, the flow of sediments changes during the irrigation season. In this article, to evaluate the canals’ carrying capacity, research in natural field conditions was carried out in the Amuzang canal belonging to the “Amu-Surkhan Irrigation Systems” basin administration. Flow transportability in natural channels was calculated for particles with d=0.05 mm by S.Kh.Abalyans, A.Zamarin, A.M.Arifzhanov, and Engelund and Hansen methods. A histogram of the dependence of flow capacity, channel depth, and average speed on the Amuzang channel was obtained, according to which it was determined that the flow capacity is 1.5-1.8 kg/m 3 in the range of 0.6-0.8 m/s.